High-alkaline water-splitting activity of mesoporous 3D heterostructures: an amorphous-shell@crystalline-core nano-assembly of Co-Ni-phosphate ultrathin-nanosheets and V- doped cobalt-nitride nanowires - Singh, Thangjam Ibomcha; Maibam, Ashakiran; Cha, Dun Chan; Yoo, Sunghoon; BabaRao, Ravichandar; Lee, Sang Uck; Lee, Seunghyun (Advanced Science, 2022)
Introducing amorphous and ultrathin nanosheets of transition bimetal phosphate arrays that are highly active in the oxygen evolution reaction (OER) as shells over an electronically modulated crystalline core with low hydrogen absorption energy for an excellent hydrogen evolution reaction (HER) can boost the sluggish kinetics of the OER and HER in alkaline electrolytes. Therefore, in this study, ultrathin and amorphous cobalt-nickel-phosphate (CoNiPOx) nanosheet arrays are deposited over vanadium (V)-doped cobalt-nitride (V-3%-Co4N) crystalline core nanowires to obtain amorphous-shell@crystalline-core mesoporous 3D-heterostructures (CoNiPOx@V-Co4N/NF) as bifunctional electrocatalysts. The optimized electrocatalyst shows extremely low HER and OER overpotentials of 53 and 270 mV at 10 mA cm(-2), respectively. The CoNiPOx@V-3%-Co4N/NF (+/-) electrolyzer utilizing the electrocatalyst as both anode and cathode demonstrates remarkable overall water-splitting activity, requiring a cell potential of only 1.52 V at 10 mA cm(-2), 30 mV lower than that of the RuO2/NF (+)/20%-Pt/C/NF (-) electrolyzer. Such impressive bifunctional activities can be attributed to abundant active sites, adjusted electronic structure, lower charge-transfer resistance, enhanced electrochemically active surface area (ECSA), and surface- and volume-confined electrocatalysis resulting from the synergistic effects of the crystalline V-3%-Co4N core and amorphous CoNiPOx shells boosting water splitting in alkaline media.
Keywords: core-shell; hydrogen productions; metal nitrides; metal phosphates; synergistic effect; water-splitting